Communicative Value of Hindu Leadership Philosophy in Kakawin Nitisastra - Gede Wirasatya (Bali Tourism Journal, 2025)
This paper explores Kakawin Nitisastra, a classical Old Javanese text, through the lens of the Aristotelian Model of Communication. Originating from ancient Indian philosophy and further developed in Balinese cultural contexts, Nitisastra integrates moral, political, and rhetorical principles to guide ethical leadership and communication practices. The study analyzes key teachings such as Catur Pariksa, Asta Brata, and Panca Upaya Sandhi, which emphasize the ethical use of speech, justice, wisdom, and strategic decision-making. These doctrines are examined in relation to Aristotle’s rhetorical triad—ethos, pathos, and logos—as well as his five communicative elements: speaker, speech, occasion, audience, and effect. Employing a qualitative descriptive method, the research draws from textual interpretation and literature review to identify the communicative values embedded in the kakawin. The analysis reveals that the speaker in Nitisastra is portrayed as a morally upright and spiritually attuned figure, whose messages are framed in culturally significant occasions and intended for a broad audience including rulers and common citizens. The effect of communication in the text, aligned with pathos, is demonstrated through its transformative influence on leadership behavior and societal ethics. The kakawin does not merely offer normative guidance but presents practical models of rhetorical and ethical engagement relevant across generations. Ultimately, this study highlights how traditional Southeast Asian literary works can embody and enrich classical communication theories, positioning Kakawin Nitisastra as both a historical artifact and a living guide for ethical leadership and public discourse.